Women Empowerment Program and Women’s Health: A Papua and Eastern Indonesia Case Study - Gobay, Maria Yuvita; Sugiyanto, Catur (Jurnal Ilmu Ekonomi Terapan, 2025)
The research examines the role of the PKK program in promoting women’s health. This research uses a quantitative approach, analyzing secondary cross-sectional data from the Indonesian Family Life Survey (IFLS) East, 2012 using the Probit model. The research seeks to address existing gaps in the literature related to the role of women empowerment programs in enhancing health outcomes in underserved and underdeveloped areas of Indonesia. As a result, the findings reveal that the family group program (dasawisma) involving ten to twenty households has a significant and positive effect on women’s health. Participants in this program show a higher probability of being in good health compared to non-participants. On the contrary, participation in the medicinal herb garden and health fund programs does not have a significant effect on improving women’s health in Papua and eastern regions. Furthermore, higher education levels and urban residency positively influenced women’s health, whereas age and distance to health facilities negatively affected health status